Otherworldly Space in Novel by Lyudmila Ulitskaya “Kukotsky Enigma” - E. A. Khudenko (Tsentr nauchnykh i obrazovatelnykh proektov, 2021)
The features of the image of the otherworldly space in the novel “The Kukotsky Enigma” are considered. The relevance of the topic is due to Lyudmila Ulitskaya’s understanding of the text as a tool with which one can “see the otherworldly”. The concepts of “otherworldly” and “otherworldly space” have been differentiated. The main principles of the image of the otherworldly space in the novel are highlighted: mirroring, carnivalization, its timeless arrangement. Attention is paid to the level organization of space in the novel. The mythologemes of water, sand and fire as fillers of space are investigated. It is noted that the novel “The Kukotsky Enigma” is characterized by the connection of the other world with reality through a number of border spaces: dreams, motives of water and illness. It is noted that the water in the novel is a “portal” to the other world, in which it is transformed into sand; the possibility of rebirth in the Middle World, the author solves the problems of the moral and philosophical order. It is concluded that the Middle World desert is associated with the female womb, where the characters are experiencing a new birth. It is shown that the space also determines the change of the onomapoetic code: the characters traveling in the Middle World change their names to nicknames, and the names remain with the characters who crossed the border of no return and remained permanent inhabitants of the other world.